A United Nations Renaissance What the UN is, and what it could be - Trent, John E. (Verlag Barbara Budrich, 2017)
This short introduction to the United Nations analyzes the organization as itis today, and how it can be transformed to respond to its critics. Combiningessential information about its history and workings with practical proposalsof how it can be strengthened, Trent and Schnurr examine what needs to bedone, and also how we can actually move toward the required reforms. Thisbook is written for a new generation of change-makers ó a generation seekingbetter institutions that reflect the realities of the 21st century and that can actcollectively in the interest of all.